Computational study on pyrolysis mechanism of β-5 linked lignin dimers - LI Wentao; GAO Lijuan; ZHOU Guanzheng; CHAI Baohua; WANG Meijing; HU Bin*; LIU Ji; LU Qiang (能源环境保护)
Lignin is a highly complex amorphous three-dimensional network polymer connected by C—O bond and C—C bond. Understanding the bond cleavage mechanism during lignin pyrolysis is crucial for advancing efficient pyrolysis technology, as it serves as a significant avenue to harness lignin′s potential. In this paper, the density functional theory method was employed to investigate the process of alignin dimer model compound that contains β-5 linkages. The calculation results show that the most likely initial reaction is the five-membered ring-opening reaction between benzene rings, in which the bond dissociation energies (BDEs) of the Cα—O bond and Cα—Cβ bond are 163.9 kJ/ mol and 212.9kJ/ mol, respectively. These reactions are the main ring-opening reactions. By comparing the cleavage of β-5 linkages among the dimers that carry methyl, methoxy, hydroxyl, n-propyl, and other branched chains, it is found that the BDEs of the Cα—O bond and Cα—Cβ bond are at a minimum when hydroxyl, propyl, and hydroxymethyl groups are attached to the two benzene rings and the five-membered ring, respectively. Homolytic cleavage of the Cα—O bond is always the initial reaction, and the continuous fracture of the Cα—O and Cα—Cβ bonds is the main path to break the five-membered ring.